Ulnar and Median Fascicular Transfers for Elbow Flexion-Predicting Outcomes in a Heterogeneous Patient Group and Implications for Surgical Planning - Ferris, Scott; Alexander, William (Frontiers in Surgery, 2020)
Purpose: To measure the outcomes in patients undergoing nerve transfers for elbow flexion restoration, and compare patient outcomes based on the pre-operative fascicular transfer plan. Methods: Single surgeon series of 48 consecutive patients who underwent median and/or ulnar fascicular nerve transfers for elbow flexion restoration to treat palsies of the brachial plexus or musculocutaneous nerve. Outcomes measured were Medical Research Council (MRC) power grade, strength in kilograms, and time taken to recover function. Results: Overall, 96% of patients achieved MRC M4 or greater power. The subgroup who were planned for, and particularly those who then underwent, double as opposed to single fascicular transfer, had significantly better results. Conclusions: Overall results were excellent. Double fascicular transfers were superior, with no failures in this group. If pre-operatively a single fascicle transfer alone is planned due to a paucity of expendable donors, the predicted outcomes are worse and other treatment options should be considered.